The impact of lesion complexity on no-reflow phenomenon and predictors of reversibility in patients treated with primary percutaneous intervention. Issue 8 (December 2020) - Durmaz, Eser; Karadag, Bilgehan; Ikitimur, Baris; Atici, Adem; Koca, Damla; Mutlu, Deniz; Soysal, Ali Uğur; Raimoglu, Utku; Ozmen, Emre; Ohtaroglu Tokdil, Kardelen; Incesu, Gunduz; Ongen, Zeki
Abstract : Objectives: Complex coronary lesions are more prone to complications; however, the relationship between complex coronary lesions and no-reflow phenomenon in patients undergoing primary percutaneous intervention (pPCI) is still not clarified. Previous studies reported the association of total coronary artery complexity with no-reflow; however, impact of culprit lesion complexity on no-reflow is not known. In this study, we aimed to investigate the impact of culprit lesion complexity on no-reflow phenomenon. Furthermore, we aimed to investigate the factors that are related to reversibility of no-reflow. Methods: We prospectively included 424 patients treated with pPCI. Patients' baseline characteristics and clinical variables were recorded. Reversibility of no-reflow was decided according to final angiography or ST resolution during the first hour following pPCI. There were 90 patients with a diagnosis of no-reflow constituted group 1 and patients without no-reflow constituted group 2. Complexity of coronary artery disease was assessed with SYNTAX score and culprit lesion complexity was assessed with both American College of Cardiology/Society of Cardiovascular Angiography and Interventions lesion classification and SYNTAX score. Results: Complexity of culprit lesion was significantly higher in group 1 patients (type C lesion 76.6 vs. 27.8%; P  < 0.001 and SYNTAX score 8.7 ± 3.0 vs. 6.2 ± 2.6; P  < 0.001, respectively, group 1 vs. 2). Multivariate analyses revealed that lesion complexity is independently associated with no-reflow. Among 90 patients of group 1, 43 patients were classified as reversible no-reflow. Logistic regression analysis revealed that only ischaemia duration is independently associated with reversibility of no-reflow. Conclusion: Our study demonstrated that culprit lesion complexity is independently associated with no-reflow phenomenon and short ischaemic duration is significantly associated with reversibility of no-reflow. Abstract : Supplemental Digital Content is available in the text.